Evidence for Residual Immunity to Smallpox After Vaccination. Issue Volume 34:Issue s1(2019) (May 2019) - Kunasekaran, Mohana; Chen, Xin; Costantino, Valentina; Chughtai, Abrar; MacIntyre, Raina
Abstract : Introduction: Smallpox has been eradicated, but advances in synthetic biology have increased the risk of its re-emergence. Residual immunity in individuals who were previously vaccinated may mitigate the impact of an outbreak, but there is a high degree of uncertainty regarding the duration and degree of residual immunity. Methods: A systematic literature review using the PRISMA criteria was conducted to quantify the duration and extent of residual immunity to smallpox after vaccination. 29 papers related to quantifying residual immunity to smallpox after vaccination were identified. Results: Duration of protection of >20 years was consistently shown in the 16 retrospective cross-sectional studies, while the lowest estimated duration of protection was 11.7 years among the modeling studies. Childhood vaccination conferred longer duration of protection than vaccination in adulthood. Multiple vaccinations did not appear to improve immunity. Most studies suggest a longer duration of residual immunity (at least 20 years) than assumed in smallpox guidelines. Estimates from modeling studies were less but still greater than the 3-10 years suggested by the WHO Committee on International Quarantine or US CDC guidelines. These recommendations were probably based on observations and studies conducted while smallpox was endemic. The cut-off values for pre-existing antibody levels of >1:20 and >1:32 reported during the period of endemic smallpox circulation may not be relevant to the contemporary population but have been used as a threshold for identifying people with residual immunity in post-eradication era studies. Discussion: Of the total antibodies produced in response to smallpox vaccination, neutralizing antibodies have shown to contribute significantly to immunological memory. Although the mechanism of immunological memory and boosting is unclear, revaccination is likely to result in a more robust response. There is a need to improve the evidence base for estimates on residual immunity to better inform planning and preparedness for re-emergent smallpox.